Secrets of Psychosocial School Planning from the Multilevel Whole-School Approach: A Qualitative Study; [Secretos de la Planificación Psicosocial Escolar Desde el Modelo de Escuela Total Multinivel: Un Estudio Cualitativo] - Rojas-Andrade, R; Prosser-Bravo, G (Pontificia Universidad Catolica de Chile, 2025)
Planning is key in education as it allows for the coordination and guidance of actions towards common goals. Unfortunately, there is little overall evidence on this topic, and even less on how psychosocial teams structure and execute their action plans. This study explored the underlying aspects of school psychosocial planning in an educational district in Chile that implements the Multi-Tiered System of Support (MTSS) model. The study follows a qualitative methodology, using a Narrative Workshop that allowed 59 psychosocial professionals to express their experiences without fear of judgment. To ensure anonymity and a confidential environment, participants were asked to write "secret letters" related to their planning process. This resulted in 96 secret letters, which were collected and categorized into two main themes and six subthemes. The findings indicate that some professionals plan with limited evidence, in isolation, and with minimal institutional validation. Additionally, planning tends to be done hastily and lacks sufficient data. These issues align with a general devaluation of the planning process. As a conclusion of the study, areas for improvement in school psychosocial planning highlight the importance of creating safe spaces for the expression of hidden experiences that may impact the effective implementation of plans. © 2025 PEL.